(untitled) (Jurnal Bina Praja, 2024)
This research analyzes the Bogor Regency government’s efforts to increase the number of tourists through digital marketing with the Ekabo application service. Then, advise on managing the Ekabo Application for the Bogor Regency regional government. After the COVID-19 recovery, tourism has become an indicator of economic development. Likewise, Bogor Regency has potential in tourism management. The Ekabo application is an innovative tourism weapon for the Bogor district government. This breakthrough application responds to the inequality in tourism quality in Bogor Regency, which tends to be centralized in one area. Based on this research, the author sees an opportunity to maximize this application by getting an upgrade in local revenue in the tourism sector. However, the implementation of the Ekabo application experienced several obstacles, such as uneven socialization due to the large size of the Bogor district. Tourism activists need to gain more awareness about the importance of promoting tourism through digital means. Then, the bad internet connection in several border areas is often a complaint from tourists, and the active participation of tourism managers needs to be higher. Therefore, the author offers several proposed strategies so that the Ekabo application can be known by foreign and local tourists, including strengthening the Ekabo application on all well-known social media as digital promotions, collaborating with tourism content creators as well as making brand ambassadors, and recording tourists’ attractions by the cultural and tourism collaborates with tourism activists in the field.